OP0136 Baseline Characteristics of Patients with Active Systemic JIA Successfully Discontinuing Corticosteroid while Receiving Canakinumab: Secondary Analysis from a Pivotal Phase 3 Trial. (23rd January 2014) - Ruperto, N.; Brunner, H.; Constantin, T.; Wulffraat, N.; Horneff, G.; Anton, J.; Berner, R.; Corona, F.; Cuttica, R.; Desjonqueres, M.; Fischbach, M.; Alessio, M.; et al.
Abstract : Background: Interleukin-1β (IL-1β) is a key driver in the pathogenesis of systemic juvenile idiopathic arthritis (SJIA). Canakinumab (CAN), a selective fully human anti-IL-1β monoclonal antibody, has been shown to be efficacious in the treatment of SJIA. 1 Corticosteroids (CS) are a mainstay of therapy for SJIA, however due to the well-known long-term side effects, reduction of CS dosage is desirable. Objectives: To assess patient features that are associated with CS discontinuation with CAN therapy. Methods: As part of the Phase 3 program of CAN, patients (2-19 years of age) with active SJIA received s.c. CAN (4mg/kg to 300 mg max) every four weeks during the maximum 20-week CS-tapering phase. 1 CS tapering was to be initiated when at least an adapted ACR50 was achieved and no fever. Here, we present the data specific to CS discontinuation as they pertain to patient baseline features. Results: At baseline 128/177 patients used CS, the median CS dose was 0.27 mg/kg/day (range: 0.02, 1.00). A total of 92/128 (72%) patients using CS at baseline entered the CS-tapering phase, and 57/128 (44.5%; p<0.0001; 90%CI; 37.1, 52.2) 1 qualified as CS-tapering successes (primary endpoint). At the end of CS-tapering phase 42 patients were CS-free and 24 had CS dose ≤0.2 mg/kg/day (a secondary endpoint). The 42 patients achieving CS-free status vs. CS users at baseline (n=128) were somewhat older (median age 9 vs. 8 years, and 7/42 [16.7%] vs. 39/128 [30.5%] were <6 years). Additionally, the CS-free patients (n=42) vs. all CS patients (n=128) had at baseline [values are all median (interquartile range)]: fewer joints with active arthritis, 7 (10) vs. 11 (20); lower physician's global assessment of disease activity, 62 (24) vs. 71.5 (25); limited range of motion (LROM) of 5.5 (10) vs. 10 (25). Conversely, gender, race, and duration of SJIA, CRP, number of flare during the preceding 6 months or specific systemic features (hepatosplenomegaly, lymphadenopathy or serositis) at baseline did not appear to differ between the two groups. Additional information about association of CS-free status and initial CAN response as well other laboratory baseline features will be provided. Conclusions: Canakinumab allowed for successful tapering of CS within 20 weeks in a sizable portion of patients with SJIA and active systemic features requiring CS for disease control. Successful CS discontinuation was more common among somewhat older patients and those with lower physician global ratings, and fewer active and limited joints at baseline. References: Ruperto N. et al. N Engl J Med 2012;367:2396-406. Disclosure of Interest: N. Ruperto Grant/research support from: Abbott, Astrazeneca, Bristol-Myers Squibb, Centocor Research & Development, Eli Lilly and company, Francesco Angelini s.p.a., Glaxo Smith & Kline, Italfarmaco, Merck Serono, Novartis, Pfizer Inc., Regeneron, Roche, Sanofi Aventis, Schwarz Biosciences GmbH, Xoma, Wyeth Pharmaceuticals Inc., Speakers bureau: Abbott, Boehringer, Bristol-Myers Squibb, Novartis, Astellas, Italfarmaco, MedImmune, Pfizer, Roche, H. Brunner Consultant for: Fee for serivce agreement with NOVARTIS for coordinating center function with payment ot CCHMC, T. Constantin: None Declared, N. Wulffraat Grant/research support from: Roche, Abbott, Consultant for: Novartis, Pfizer, Roche, G. Horneff Grant/research support from: Abbott, Pfizer, Roche, Speakers bureau: Pfizer, Abbott, Roche, J. Anton Grant/research support from: Pfizer, Consultant for: Novartis, Roche, Abbott, Speakers bureau: Novartis, Abbott, SOBI, R. Berner Grant/research support from: Novartis, F. Corona: None Declared, R. Cuttica: None Declared, M. Desjonqueres: None Declared, M. Fischbach: None Declared, M. Alessio: None Declared, A. Chieng: None Declared, W. Emminger: None Declared, E. Haddad: None Declared, K. Lheritier Shareholder of: Novartis, Employee of: Novartis, K. Abrams Shareholder of: Novartis, Employee of: Novartis, J. Hruska Employee of: Novartis, D. Kim Shareholder of: Novartis, Employee of: Novartis, A. Martini Grant/research support from: Abbott, Astrazeneca, Bristol-Myers Squibb, Centocor Research & Development, Eli Lilly and Company, Francesco Angelini s.p.a, Glaxo Smith & Kline, Italfarmaco, Merck Serono, Novartis, Pfizer Inc, Regeneron, Roche, Sanofi Aventis, Schwarz Biosciences GmbH, Xoma, Wyeth Pharmaceuticals Inc, Speakers bureau: Abbott, Bristol-Myers Squibb, Astellas, Boehringer, Italfarmaco, Medimmune, Novartis, Pfizer, D. Lovell Grant/research support from: National Instituesof Health, Consultant for: Astra-Zeneca Pharmaceutical, Centocr Inc, Wyeth Pharmaceuticals, Amgen, Bristol-Myers Squibb, Abbott, Pfizer, Regeneron, Hoffmann;La Roche Inc, Novartis, UBC, Forest Research Med, Employee of: Cincinnati Childrens Hospital Medical Center, Speakers bureau: Wyeth